Prevalência e fatores associados a coinfecções entre mulheres vivendo com HIV/AIDS em estado do Nordeste do Brasil - Silva, Brenda Evelin Barreto da (2020)
Introduction: the impact of the biological interaction between Human Immunodeficiency Virus (HIV) and coinfections is widely discussed in the world context. Objective: to verify the prevalence of coinfections in women living with HIV/AIDS in a state in northeastern Brazil. Methods: A cross-sectional study was conducted at reference outpatient clinic for people living with HIV/AIDS in Sergipe state between August 2014 and November 2017. A total of 435 HIV-positive women were followed-up at the clinic. After interview, clinical reports and laboratory tests of syphilis, hepatitis B and C, toxoplasmosis, rubella and cytomegalovirus were verified. HIV-Tuberculosis coinfection was analysed by record linkage with the SINAN/Sergipe database with reported tuberculosis cases in women between 2001 and 2017. For the molecular diagnosis of human papillomavirus (HPV), samples of the endocervical canal were collected of 270 women participating in the study. DNA was extracted and amplified by the Polymerase Chain Reaction technique and genotyping was performed by sequencing the positive samples. Descriptive statistics and bivariate analyses were performed to measure associations between independent variables and occurrence of coinfections. Results: Among 435 HIV-positive women, the median (interquartile range) age was 38 (30-46) years old; 209 (48.5%) had 0-4 years of schooling; 280 (67.6%) were in marital union; and 191 (45.4%) had their first sexual intercourse under 15 years old. Being black (Prevalence Ratio (PR) 1.58, 95% CI= 0.75-3.33), acquiring HIV through sexual intercourse (PR=1.58, 95% CI= 0.80-2.73), having first sexual intercourse under the age of 15 (PR=1.51, 95% CI= 0.93-2.45), and having sex for money (PR=1.76, 95% CI=0.88-3.50) were predictors of coinfection. The prevalences of coinfections identified in this study were: 9.1% for syphilis (38/419), 3.9% for tuberculosis (17/435), 3.8% for toxoplasmosis (13/340), 2.5% for hepatitis C (10/401), 2.3% for hepatitis B (9/394) and 1.8% for rubella (5/280). In addition, seropositivity for IgG antibody against cytomegalovirus (96.2%), rubella (90%) and toxoplasmosis (71.2%) were detected. Among the 270 women who underwent the HPV-DNA detection test, 150 (5.6%) were positive. Twenty- four viral types were identified, 113 (72%) had high risk of oncogenicity HPV and the most prevalent was HPV 16 (53/35.3%), followed by: HPV 6, 31, 33 and 35 (9/6%, each). Positive 12 HPV status was statistically associated with having 4-8 years of schooling (Odds Ratio (OR)= 3.03; 95%CI=1.45-6.53; P=0.002) and having been diagnosed less than five years ago (OR=1.90; 95%CI=1.06-3.40; P=0.027). Among 231 women, 31 (13.4%) had cytological abnormalities, most of them with high-grade squamous intraepithelial lesions (16/51.6%). Of the 200 (86.6%) who were negative for lesions and malignancy on cytology, 99 (49.5%) were HPV DNA positive. Conclusions: syphilis and HPV were the most prevalent coinfections, which shows a higher vulnerability to sexually transmitted infections. In addition, a large diversity of HPV genotypes was detected, of which HPV 16 was the most prevalent. Thus, the information obtained in this study can help strengthen public policies for prevention and diagnosis of coinfections directed at the female population living with HIV/AIDS in Sergipe.